Thinking Process of Concrete Student in Solving Two-Dimensional Problems - Sri Adi Widodo; Ambar Dana Pangesti; Istiqomah Istiqomah; Krida Singgih Kuncoro; Tri Astuti Arigiyati (Universitas Sriwijaya, 2020)
The purpose of this research was to find out the thinking processes of a concrete student in solving two-dimensional problems. The research method used is descriptive qualitative. The research subjects were two students taken using purposive sampling. The instrument used was the Test of Logical Operations and problem-solving tests. Stages of data analysis used are researching all data, making a cognitive classification of students, choosing concrete students to be used as research subjects, reviewing the results of concrete student work in solving mathematical problems, verify data and data sources that have been classified and transcribed in the presentation or exposure of data. The results showed that at the stage of understanding the problem and re-checking the answers, concrete students use the assimilation at the stage of planning to solve the problem of doing the disequilibration. At the stage of carrying out a plan to solve a problem, concrete students carry out the accommodation. During this study, it was found that students 'habits in mathematical problem-solving did not plan to solve problems, did not re-examine answers, and there were students' habits by interpreting the final results of problems. It can be concluded that the students' concrete thinking processes in solving two-dimensional problems vary according to the stages of problem-solving.